Leadership Based on the Four Iddhipada Principles Affecting the Core Mission Administration of Educational Institutions Under the Nakhon Pathom Primary Educational Service Area Office 2 - Wongwikarn, Yaowaluck; Saengmookda, Suthasinee (Journal of Dhamma for Life, 2026)
The objectives of this thesis were: 1) to study the leadership of school administrators based on the Four Paths of Accomplishment (Iddhipada 4), 2) to examine the level of school administration tasks, and 3) to investigate the leadership based on the Four Paths of Accomplishment that affects school administration tasks under the Nakhon Pathom Primary Educational Service Area Office 2. The research sample consisted of 92 schools. The informants were 368 personnel, including school directors, heads of academic affairs, and teachers. The research instrument was a questionnaire. Data were analyzed using frequency, percentage, mean, standard deviation, and multiple regression analysis. The research findings revealed that: 1) The overall leadership based on the Four Paths of Accomplishment of school administrators was at a high level. Considering each aspect, the highest mean was Perseverance (Viriya), followed by Will (Chanda), Attentiveness (Citta), and Reflection (Vimamsa), respectively. 2) The overall school administration tasks were also at a high level. The aspect with the highest mean was school quality administration, followed by teacher and staff development, environment and service management, and curriculum and academic administration, respectively. 3) Leadership in Reflection (Vimamsa) and Attentiveness (Citta) statistically significantly affected school administration tasks at the .01 level. The multiple regression predictive equations could be written in raw score and standardized score forms as follows: Raw Score Equation: = 2.702 + .232 + .155 Standard Score Equation: = .355 ( ) + .237 ( )